A Photoswitchable Triple Chemosensor for Cyanide Anion Based on Dicyanovinyl‐Functionalized Dithienylethene. Issue 22 (5th June 2019) - Li, Ziyong; Dai, Yijie; Lu, Zhiqiang; Pei, Yingying; Song, Yufei; Zhang, Lilei; Guo, Hui
Abstract : The development of new sensors for the accurate detection of cyanide anion has attracted more and more attention due to their potential applications in environmental and biological systems. Here, two novel near‐infrared (NIR) photochromic compounds 1a and 1b, which were modified by the dicyanovinyl fragment with cyanide recognition function, have been developed. Surprisingly, 1a presented an unprecedented triple sensing performance for cyanide anion (colorimetric‐fluorescent‐colorimetric), which can be utilized as a potential precision sensor for CN – in environmental and biological systems. Although 1b did not show triple detection behavior for CN –, it could recognize CN – and F – synchronously and selectively by naked eyes. Moreover, their NIR photochromic behaviors could be modulated by the cyanide anion. Their sensing mechanism for CN – or F – was confirmed by absorption spectral studies, NMR titration, and DFT calculations. Abstract : A novel photoswitchable chemosensor for cyanide anion based on dithienylethene unit was developed, which displayed excellent near‐infrared photochromism. Moreover, it presented a distinct triple sensing performance for CN – (colorimetric‐fluorescent‐colorimetric).